The Influence of Participatory Leadership On Employee Performance At The Office of Women’s Empowerment, Child Protection, And Family Planning In Tambrauw Regency, Southwest Papua - Yeremias Assem; Jeffry Sony Junus Lengkong; Romi Junior Mongdong (International Journal of Science and Environment (IJSE), 2026)
This study aims to empirically examine the influence of participative leadership on employee performance at the Department of Women's Empowerment, Child Protection, and Family Planning (DP3AKB) of Tambrauw Regency. The urgency of this study is driven by significant social service challenges, such as handling stunting and overcoming geographical constraints in the region. The research method utilizes a quantitative approach with a causal (explanatory research) design. A population of 38 employees was fully involved as respondents through a saturated sampling (census) technique. Primary data were collected via Likert-scale questionnaires, structured observations, and documentation studies, which were then analyzed using simple linear regression through SPSS software. The results show that the participative leadership style at DP3AKB is in the high enough category (average of 50.2895), while employee performance is in the good category (average of 50.2105). Hypothesis testing proves that participative leadership has a positive and significant effect on employee performance with a t-count (10.840) > t-table (2.037) and a significance level of 0.000 < 0.05. The coefficient of determination () of 0.765 indicates that the participative leadership style contributes 76.5% to the variation in employee performance. In conclusion, the implementation of inclusive leadership through open communication and staff involvement in decision-making is proven effective in increasing work productivity. Leaders are advised to optimize their role as facilitators to maintain employee motivation in achieving organizational targets.